Epitope Peptide-Based Predication and Other Functional Regions of Antigenic F and HN Proteins of Waterfowl and Poultry Avian Avulavirus Serotype-1 Isolates From Uganda - Omony, John Bosco; Wanyana, Agnes; Mugimba, Kizito K.; Kirunda, Halid; Nakavuma, Jessica L.; Otim-Onapa, Maxwell; Byarugaba, Denis K. (Frontiers in Veterinary Science, 2021)
Uganda is a Newcastle disease (ND) endemic country where the disease is controlled by vaccination using LaSota (genotype II) and I2 (genotype I) vaccine strains. Resurgent ND outbreaks call for a need to understand the antigenic diversity of circulating wild Avian Avulavirus serotype-1(AAvV-1) strains. High mutation rates and continuous emergence of antigenic variants that evade immunity make RNA viruses difficult to control. In this study, we used computational analysis, phylogenetic characterization and structural modelling to detect evolutionary forces affecting immune-dominant Fusion (F) and Hemagglutinin-Neuraminidase (HN) proteins of AAvV-1s compared to that in LaSota vaccine strain. Our findings indicate that mutational amino acid variations at the F-protein in LaSota strain, 25 poultry and 30 waterfowl wild-type isolates were distributed at the functional domains of B-cell epitopes or N-glycosylation sites, cleavage site and fusion site. Similarly, conserved regions of HN-protein in 25 Ugandan domestic fowl isolates and LaSota vaccine strain varied at the flanking regions and potential linear B-cell epitope. The fusion sites, signal peptides, cleavage sites, transmembrane domains, potential B-cell epitopes of the two protein types in vaccine and wild viruses varied considerably at structure by effective online epitope prediction programs. Cleavage site of the waterfowl isolates had a typical avirulent motif of 111GGRQGR’L117 with the exception of one isolate showing a virulent motif 111GGRQKR’F117. All the poultry isolates showed the 111GRRQKR’F117 motif corresponding to virulent strain. Amino acid sequence variations in both HN and F-proteins of the wild AAvV-1s and vaccine strain were distributed over the length of the proteins with no detectable pattern, but using the experimentally derived 3D structure data revealed key mapped mutations on the predicted conformational epitopes encompassing the experimental major neutralizing epitopes. The phylogenic tree constructed using the F-gene indicated that Ugandan NDV isolates share some functional nucleotides in F-gene yet do remain unique at the protein structure and the B-cell epitopes. Recombination analyses showed that the C-terminus and the rest of the F-gene in poultry isolates originated from prevalent velogenic strains. Altogether, these could provide rationale for antigenic diversity in wild ND isolates of Uganda compared to the current ND vaccine strains.